Structural and Magnetic Characterisations of Pb-Doped MgO Nanoparticles by a Modified Pechini Method. Issue 1 (November 2020) - Najem, Israa A.; Edrees, Shaker J.; Rasin, Fadhil Abd
Abstract: Doping magnesium oxide nanoparticles (MgO-NPs) forms a good material for magnetisation applications. The Room Temperature Ferromagnetic (RTFM) of Pb 2+ -doped ions MgO-NPs synthesised by a modified Pechini method are discussed in the present paper. The structural, morphological and magnetic properties of the samples were characterised by X-ray diffraction (XRD), Field Emission scanning electron microscopy (FE-SEM), Energy Dispersive Spectroscopy (EDS) and vibrating sample magnetometer (VSM). The XRD results showed that the synthesised materials have a single set of peaks in the XRD patterns, corresponding to the cubic phase of MgO-NPs. As the Pb content increased in the host MgO-NPs leading to an increase in the lattice parameter, the interplanar spacing and the crystallite size; however, the intensity decreased. Small spherical nanoparticles (22.87–29.05nm) were observed in the Pb 2+ -doped ions MgO samples by (FE-SEM). The purity of the samples was confirmed using EDS spectroscopy. The pure MgO and doped samples exhibiting RTFM may be attributed to vacancy defects, which caused local magnetisation. The saturation magnetism (Ms) was found to be varied as a function of doping concentration. The maximum (Ms) was found at x=0.015 of Mg0.985 Pb0.015 O sample. The obtained results suggest that both Pb doping and oxygen vacancies play an important role in the development of room-temperature ferromagnetism.